1995
DOI: 10.1080/00049539508258765
|View full text |Cite
|
Sign up to set email alerts
|

The development of children's theory of mind: The working memory explanation

Abstract: The hypothesis that a growth in working memory capacity could explain the observed development of theory of mind in preschoolers was tested. Fifty‐four 3‐ to 5‐year‐olds were administered: two false belief tasks as measures of theory of mind development; two “false” photograph tasks parallel to typical false belief tasks, but involving nonmental representations; the Peabody Picture Vocabulary Test ‐Revised (PPVT‐R); and two working memory capacity measures (backward digit span, BDS, and forward digit span, FDS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
181
0
9

Year Published

2002
2002
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 272 publications
(208 citation statements)
references
References 20 publications
18
181
0
9
Order By: Relevance
“…On the backward word span task, which assessed working memory, children were asked to repeat a list of words in backward order (Davis & Pratt, 1996). The practice list and the first list each contained two words, and subsequent lists gradually increased to a total of five words.…”
Section: Measures Of Efmentioning
confidence: 99%
See 2 more Smart Citations
“…On the backward word span task, which assessed working memory, children were asked to repeat a list of words in backward order (Davis & Pratt, 1996). The practice list and the first list each contained two words, and subsequent lists gradually increased to a total of five words.…”
Section: Measures Of Efmentioning
confidence: 99%
“…The elaborated play of older preschool children, including their ability to sustain synchronized, thematic play, and negotiate turn taking and resource sharing, reflects their growing capacity to mentally represent and follow social scripts, tracking social exchange as they go (Barkley, 2001;Nelson, 2003). Working memory is often assessed with fairly discrete cognitive tasks, such as backward word span (Davis & Pratt, 1996), in which a child must hold words in mind and repeat them in backward order.…”
Section: Measuring Ef Skill Development In the Preschool Yearsmentioning
confidence: 99%
See 1 more Smart Citation
“…Leslie & Thaiss, 1992), increases in cognitive resources allow a child to express or apply ToM abilities. In contrast, according to the view that sources can be found in the work of Case (1985), the increase of cognitive resources is not responsible for the expression, but for the development (acquisition) of ToM -the position represented later, amongst others, by Davis and Pratt (1995). All longitudinal research consistently showed that measures of working memory obtained in the earlier period of development were not significant predictors of later ToM skills.…”
Section: Important Findings In Studies On Relations Between Ef and Tommentioning
confidence: 81%
“…En effet, comme mentionné dans le contexte théorique Davis et Pratt (1996) ont examiné chez des enfants en développement, la relation entre la aussi en une seule phase concernant la production de la réponse avec rétroaction sur la situation sociale en cours. À ce modèle, il serait possible, par la suite, d'y associer un modèle neuroanatomique de la TdE, ce qui n'a pas été réalisé dans cet essai.…”
Section: Quatrième Hypothèseunclassified